Lake Taihu, China : dynamics and environmental change - Qin, Boqiang (Monographiae biologicae, 2008)
There are many shallow lakes in the world. Many of them play an important socio-economic role as contributors to the drinking water supply, in flood attenuation, fisheries and recreation activities. Because of the current anthropogenic changes in the environment, such lakes rapidly respond to eutrophication and swamping. It is often hard to address these issues because many changes in the ecosystems of shallow lakes are associated with little studied physical processes. This interaction between the aquatic biota and the physical and chemical environment increases the complexity of shallow lake.